Laboratory investigation on water quality and soil consolidation behaviour of soil- activated carbon mixture in riverbank filtration system - Pius Antonio , Ng Yew Shang (2015)
Riverbank Filtration (RBF) is an alternative water treatment process that makes use of surface water that has naturally infiltrated into groundwater through rivers or bank(s) and is extracted by using pumping well. Conventional water treatment method uses both physical and chemicals like disinfectants and coagulants to control pathogens that result in a higher cost and the use of chemicals that can cause relative health problems. In riverbank filtration system, specific natural soil properties are needed to effectively filter and extract fresh water from underground sources. Such scarcity of having the ideal soil properties has prompt the application of artificial soil barrier as an alternative source for riverbank filtration to extract fresh water from underground sources. However, the removal of natural soil and replacement of artificial soil has disturbed the soils in the area which would result in soil consolidation and settlement, and hence the overall stability of the system. Therefore, this research is carried out to investigate the compressibility behaviour of the soils. Besides, it is also carried out to determine and compare the effectiveness of natural soil and mixture of natural soil and activated carbon in treating water.